2020
DOI: 10.3390/sym12060939
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Snake Robot Locomotion Possibilities in a Pipe

Abstract: This paper analyzed the locomotion of a snake robot in narrow spaces such as a pipe or channel. We developed a unique experimental snake robot with one revolute and one linear joint on each module, with the ability to perform planar motion. The designed locomotion pattern was simulated in MATLAB R2015b and subsequently verified by the experimental snake robot. The locomotion of the developed snake robot was also experimentally analyzed on dry and viscous surfaces. The paper further describes the investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…The mathematical model of the developed robot was proposed to analyze the influence of input parameters. The simulations and experiments were presented to validate the effectiveness of the proposed method and prototype [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical model of the developed robot was proposed to analyze the influence of input parameters. The simulations and experiments were presented to validate the effectiveness of the proposed method and prototype [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the anti-slip properties of a road surface are investigated and evaluated before commissioning [6]. In [7][8][9], different methods of the measurement of friction forces for different applications were examined, and it was found that friction issues affect many areas of everyday life [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…To optimize the technical equipment (the bicycle itself and its mechanical properties, suspension, frame, material base, kinematics; wearing, ventilation and thermal regulation; safety elements, etc.) to reach the highest possible performance, total efficiency, and safety [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17];…”
mentioning
confidence: 99%
“…Nowadays, there is strong research being conducted in areas related to cycloengineering, e.g., in designing new frames [4,5], suspension mechanism components [6,7], stiffness analysis [8][9][10][11], kinematic and dynamic analysis [12][13][14][15], material/technology development [8,16,17], study the relationship between the bicycle and the cyclist's body [18,19] as well as safety analysis and improvement [19,20]. These topics are also related to other general areas such as medicine and healthcare, material science, aerodynamics, green energies, additive technologies, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation